Pengembangan Model Buku Kerja Siswa dalam Pembelajaran Menulis Narasi untuk Kelas IV Sekolah Dasar - Darnis Arief (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Based on in-depth observation and assessment of the needs of narrative writing in the fourth grade elementary school Padang city, it was found that learning to write the narrative has not been applied effectively. This condition can not be ignored because it affects the quality of learning Indonesian. Therefore, the development model of the workbook in learning to write effective narrative Elementary School fourth grade needs to be done. A research development consisting of analysis, design, development, implementation, and evaluation has been done in the development of the model workbook in pembel¬ajaran writing narrative for the fourth grade elementary school. This research products in the form of a workbook has been assessed by a team of experts, validated by experts and users of the product. In addition, the implementation phase conducted an assessment of the student activities and student writing. The research data consisted of quantitative and qualitative data. Data were analyzed with statistical techniques percentage. Through experimental trial data were analyzed using t-test. The findings of the study is that the model workbook in learning to write the narrative for the fourth grade primary school has been developed with the validity, effectiveness and practicality meet educational standards. Based on these findings it can be concluded that the design of the model can be used effectively in order to improve the quality of learning to write the narrative for Elementary School fourth grade students.